Transfer of Testing Research from University to Industry: An Experience Report - Güldali, Baris; Sauer, Stefan (online Proc. of International TestIstanbul Conference 2010 (URL: www.testistanbul.org/presentations.html))
Software Quality Lab (s-lab) is an open multi-private-public partnership institute for knowledge and technology transfer. In s-lab, partners from industrial software development closely cooperate with research groups of the University of Paderborn. Together with partners from industry, s-lab develops and evaluates constructive and analytical methods and tools of software engineering for obtaining high-quality software. Testing plays an important role in analytical quality assurance within s-lab’s activities. Thereby our main focus lies on the development of testing methods, test automation tools and test management concepts for the individual needs of the industrial partners. Because of the different requirements of the university and the industry; the cooperation involves some challenges, e.g. defining projects aiming at the commercial interests of the industry and addressing interesting research questions. In this paper, we give an overview of testing activities in s-lab and address targets and challenges of the cooperative work between industry and university. We also summarize the lessons learned during the numerous testing projects especially in the domain of business information systems.

Verteiltes Testen heterogener Systemlandschaften - von der Maßen, Thomas; Wübbeke, Andreas (Proceedings of Software Engineering 2010 (SE2010))

Cooperative feedback to improve capacity and error rate in multiuser diversity systems - an OFDM case study - Valentin, Stefan; Karl, Holger (European Transactions on Telecommunications)

Expected interference in wireless networks with geometric path loss: a closed-form approximation - S. Lichte, Hermann; Valentin, Stefan; Karl, Holger (IEEE Communications Letters)

Automated Development of Cooperative MAC Protocols - A Compiler-Assisted Approach - Simon Lichte, Hermann; Valentin, Stefan; Karl, Holger (Mobile Networks and Applications)

Concept and Prototype for a Real-Time Enabled Publish/Subscribe System - Andree, Matthias; Gebel, Alexander; Karl, Holger (10th IEEE International Conference on Computer and Information Technology, CIT 2010, Bradford, West Yorkshire, UK, June 29-July 1, 2010)

Risk Aware Overbooking for Commercial Grids - Birkenheuer, Georg; Brinkmann, Andre; Karl, Holger (Job Scheduling Strategies for Parallel Processing - 15th International Workshop, JSSPP 2010, Atlanta, GA, USA, April 23, 2010, Revised Selected Papers)

Fading-resistant low-latency broadcasts in wireless multihop networks: the probabilistic cooperation diversity approach - S. Lichte, Hermann; Frey, Hannes; Karl, Holger (Proceedings of the 11th ACM Interational Symposium on Mobile Ad Hoc Networking and Computing, MobiHoc 2010, Chicago, IL, USA, September 20-24, 2010)

FIT: Future Internet Toolbox - Biermann, Thorsten; Dannewitz, Christian; Karl, Holger (Testbeds and Research Infrastructures. Development of Networks and Communities - 6th International ICST Conference, TridentCom 2010, Berlin, Germany, May 18-20, 2010, Revised Selected Papers)

Prototyping with the Future Internet Toolbox - Dannewitz, Christian; Biermann, Thorsten; Dräxler, Martin; Beister, Frederic; Karl, Holger (Testbeds and Research Infrastructures. Development of Networks and Communities - 6th International ICST Conference, TridentCom 2010, Berlin, Germany, May 18-20, 2010, Revised Selected Papers)